2017
DOI: 10.1016/j.carpath.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Altered protein levels in the isolated extracellular matrix of failing human hearts with dilated cardiomyopathy

Abstract: Dilated cardiomyopathy (DCM) is associated with extensive pathological cardiac remodeling and involves numerous changes in the protein expression profile of the extracellular matrix of the heart. We obtained seven human, end-stage, failing hearts with DCM (DCM-failing) and nine human, nonfailing donor hearts and compared their extracellular matrix protein profiles. We first showed that the DCM-failing hearts had indeed undergone extensive remodeling of the left ventricle myocardium relative to nonfailing heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…with the prognosis of acute heart failure reported by Qiang et al (8), Fukushima et al (9), Fan et al (14), Goren et al (15) and Tijsen et al (16), and considering that episodes of ADHF are associated with transient increases in the blood levels of markers of cardiac myocyte injury, extracellular matrix turnover, and inflammation (17)(18)(19), possibly reflecting an acceleration of pathological myocardial remodeling (20), it was decided to measure the plasma levels of miR-21, -126 and -423-5p in patients with ADHF at the time of hospital admission to determine whether they alter during clinical improvement. The present study additionally investigated whether the levels of these three miRs were associated with all-cause mortality for a longer follow-up period (up to 48 months).…”
Section: Plasma Levels Of Microrna-21 -126 and -423-5p Alter During mentioning
confidence: 91%
“…with the prognosis of acute heart failure reported by Qiang et al (8), Fukushima et al (9), Fan et al (14), Goren et al (15) and Tijsen et al (16), and considering that episodes of ADHF are associated with transient increases in the blood levels of markers of cardiac myocyte injury, extracellular matrix turnover, and inflammation (17)(18)(19), possibly reflecting an acceleration of pathological myocardial remodeling (20), it was decided to measure the plasma levels of miR-21, -126 and -423-5p in patients with ADHF at the time of hospital admission to determine whether they alter during clinical improvement. The present study additionally investigated whether the levels of these three miRs were associated with all-cause mortality for a longer follow-up period (up to 48 months).…”
Section: Plasma Levels Of Microrna-21 -126 and -423-5p Alter During mentioning
confidence: 91%
“…Failing human heart tissues were procured as explants from patients with end-stage heart failure receiving a transplant. Details of clinical and histological data related to the nonfailing and failing heart tissues used in this study can be found in ( DeAguero et al., 2017 ). We focused on the three nonfailing and DCM-failing human hearts that were used to generate the proteomics data in ( DeAguero et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Decellularized tissue was flash frozen and lyophilized. Complete decellularization was confirmed by Masson's trichrome staining of ECM tissue sections ( DeAguero et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have hitherto been published concerning, among other issues, protein alterations in conditions such as dilated cardiomyopathy, myocardial hypertrophy, atherosclerosis, atrial fibrillation and myocardial stunning, the identification of biomarkers in ischaemic heart disease and the acquisition of mechanistic insights into myocardial protection during ischaemia and reperfusion . In heart failure (HF), proteome analyses have revealed changes concerning proteins of the extracellular matrix, cardiomyocyte cytoskeleton, contractile apparatus, energy production and cardiomyocyte protection that are up‐ or down‐regulated ( Table ) …”
Section: Key Human Studies On Proteomics In Heart Failurementioning
confidence: 99%